Analisis Pengaruh Bekerja dari Rumah dan Bekerja dari Kantor terhadap Kepuasan Kerja dan Produktivitas Kerja Karyawan Perusahaan - Heima Sitorus; Harman Malau (BUDGETING : Journal of Business, Management and Accounting, 2023)
Covid-19 or Coronavirus Disease is still the center of attention throughout the world today. One of the PT x companies in Bandung, West Java, which is engaged in technology (software house) since entering the new normal era, the company has not implemented work from home and directly applies the work from office process. The data collection method uses a questionnaire with descriptive analysis techniques. The sample population of this study was 45 samples with purposive sampling technique. Data testing is done with descriptive test, T test, F test, Determination Coefficient Test. This study states that if the value of wfh and wfo is 0, the value of Employee Performance is 34.191. This means that every employee working from the office, will increase Employee Performance by 0.144. While employees work from wfo, it will increase Employee Performance by 1.128. If the value of wfh and wfo is 0, the productivity value of employee performance is 34.833. This means that every employee working from the office will increase employee performance productivity by 0.122, and every employee working from wfo will increase employee performance by 0.136. Keywords: Performance, Productivity, Work From Home, Work From Office.